Speed test analysis of LTE mobile networks in Malaysia / Nurfairuz Zafirah Fuad - Fuad, Nurfairuz Zafirah (2017)
Despite the huge growths in the mobile network with the LTE technology usage, the network operators are facing challenges to provide the best mobile network for the users. LTE technology is the key elements for mobile operators to provide the best mobile network to their users. Different mobile operators provide a difference network performance to the mobile users. Based on the speed test, this study investigates on what factors that can impact the network performance of LTE technology. Mobile users are facing different experience in mobile network coverage. Users received varying LTE signal in their devices at different locations. This paper focuses on which mobile operators provide the best network performances to their mobile users. Besides drive test, LTE performance can also be measured by a speed test. This paper represented the LTE network performance from the speed test analysis of two different types of smartphones. This speed test of LTE mobile network is based on the three major mobile operators in Malaysia which are Celcom, Maxis and Digi. Speed test is performed by 'Speed test by Ookla' and "OpenSignaP mobile applications. The parameters of speed test are calculated based on latency, download and upload speed. This speed test is performed anywhere and anytime in Malaysia. This is to prove the users' behavior of using LTE mobile network. The results presented the average speed of the LTE network in Malaysia based on the top three mobile operators in Malaysia such as Ceicom, Digi and Maxis. In this paper, we analyzed the factors that impact the LTE network performance based on the results collected. We also analyzed the best coverage and LTE network performance based on the lower latency, higher download speed and upload speed. The data analyzation method is also discussed and the results from the analysis will be presented. Finally, a report based on the overall conducted study will be written together with conclusion and recommendation of future.